Application of solar energy to seawater desalination in a pilot system based on vacuum multi-effect membrane distillation. (15th January 2020) - Andrés-Mañas, J.A.; Roca, L.; Ruiz-Aguirre, A.; Acién, F.G.; Gil, J.D.; Zaragoza, G.
Highlights: Assessment of a pilot-scale solar vacuum multi-effect membrane distillation system. Use of heat storage allowed operating with discontinuous solar radiation. Different operational strategies depending on heat temperature setpoint assessed. Total annual production of 70.5 m 3 distilled water with 35.9 m 2 solar field. Abstract: The evaluation of a novel solar seawater desalination system implemented at the University of Almeria (Spain) is presented. It integrates a solar thermal field based on static collectors and a thermal desalination system based on the vacuum multi-effect membrane distillation technology. The distillation unit has a particular innovation to increase its thermal performance, using a seawater flow to condense the steam and preheat the feed. Experiments were made under different environmental conditions to assess the role of the thermal storage system for minimizing the effect of disturbances in solar radiation. Thermal energy could be delivered at a stable temperature to the distillation module, even with variable solar radiation. A simulation analysis based on a quasi-dynamic model was also performed to evaluate the distillate production profile and the operating time during a typical year considering different temperature setpoints at the inlet of the membrane module (60, 70, and 80 °C). The simulated volume of distilled water generated annually ranged from 41.7 to 70.5 m 3, depending on the setpoint. The membrane distillation unit produced water almost uniformly along the year, with an average flux of (5.5 ± 1) l h −1 m −2 at the maximum setpoint, which was proved the most favourable.